Mulberry-like BiVO4 architectures: synthesis, characterization and their application in photocatalysis. Issue 22 (19th May 2021) - Wei, Jiangang; Wang, Xiaoyu; Li, Wenqin; Li, Yihuai; Zhu, Xiangrong; Zhu, LuPing
Abstract : Mulberry-like BiVO4 architectures were prepared by a facile solvothermal route. The obtained architectures showed enhanced light absorption, high photocatalytic properties, good stability and reusability. Abstract : In this work, mulberry-like BiVO4 architectures were successfully prepared by a facile solvothermal route. Morphology and structure characterizations reveal that the as-obtained mulberry-like BiVO4 architectures have a well-crystallized monoclinic scheelite structure with good dispersion and uniformity. The effect of the solvent ratio on the morphology, structure, and performance of the samples was systematically investigated. The photocatalytic properties of the as-obtained BiVO4 samples were studied in detail. The as-prepared mulberry-like BiVO4 architectures showed enhanced photocatalytic activity, which should be attributed to their large surface area, enhanced light absorption, and distinctive morphology. The photoluminescence (PL) spectroscopy, electrochemical impedance spectroscopy (EIS) and photocurrent density test show that the mulberry-like structures can promote the charge transfer and separation efficiency of the photogenerated carriers in the as-synthesized BiVO4 samples. In addition, the obtained mulberry-like BiVO4 architectures show good stability and reusability. This work can provide a new strategy for the controllable synthesis of hierarchical structures and the enhancement of light absorption and photocatalytic activities.